THE USE OF SULFUR-CONCRETE IN REINFORCED CONCRETE STRUCTURES - Akhmedov Islombek; S.Kholmirzayev; Umarov Isroil; B.Sharopov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. the article presents the results of experimental studies on the physical and mechanical properties of sulfur concrete and the comparative characteristics of the strength and deformation properties of sulfur concrete with concrete based on Portland cement. The results of theoretical studies on the use of sulfur concrete in reinforced concrete structures are highlighted.